Dialoghi d'artista : Incontri con l'arte contemporanea 1970-1984. - Bonito Oliva, Achille; Borges, Jorge Luis, 1899-1986. (Milano : Electa Editrice Milano, 1984)
Beuys, Joseph ; Warhol, Andy ; Turcato, Giulio ; Pistoletto, Michelangelo ; Nauman, Bruce ; LeWitt, Sol ; Morris, Robert ; Ryman, Robert ; Fabro, Luciano ; Andre, Carl ; Smithson, Robert ; Acconci, Vito ; Tuttle, Richard ; Gilbert & George ; Kosuth, Joseph ; Buren, Daniel ; Barry, Robert ; Wilson, Jan ; Weiner, Lawrence ; Paolini, Giulio ; Boetti, Alighiero ; Toroni, Niele ; Kounellis, Jannis ; Merz, Mario ; Fox, Terry ; Pisani, Vettor ; Chia, Sandro ; Cucchi, Enzo ; Clemente, Francesco ; De Maria, Nicola ; Paladino, Mimmo
Italiaans & Engels
boek
Keywords: Acconci, Vito; Andre, Carl; Barry, Robert; Beuys, Joseph; Boetti, Alighiero; Buren, Daniel; Chia, Sandro; Clemente, Francesco; Cucchi, Enzo; De Maria, Nicola; Fabro, Luciano; Fox, Terry; Gilbert & George; Kosuth, Joseph; Kounellis, Jannis; LeWitt, Sol; Merz, Mario; Morris, Robert; Nauman, Bruce; Paladino, Mimmo; Paolini, Giulio; Pisani, Vettor; Pistoletto, Michelangelo; Ryman, Robert; Smithson, Robert; Toroni, Niele; Turcato, Giulio; Tuttle, Richard; Warhol, Andy; Weiner, Lawrence; Wilson, Ian